Impacto do valor de uso, da sustentabilidade e do ambiente construído,na disposição a pagar por edificações residenciais sustentáveis - Petroli, Ângela (My University, 2024)
The increase in population in urban centers is causing more and more problems for the environment: reduction of green areas, air and water pollution, climate change. This increase brings a greater need for residential property, stimulating the construction industry and making companies in the sector more competitive. It is therefore essential for the construction industry to become more sustainable by minimizing its impact on the environment, as well as to better understand the consumer's relationship with sustainability concepts so that companies can target their investments assertively and win customers. This research investigates the relationship between the dimensions of sustainability and the built environment with the dimensions of sustainable building consumer behavior: willingness to pay, purchase intention, use value and word of mouth. The research is quantitative-descriptive in nature using a survey, applied to multi-family buildings in a city in the Serra Gaucha region (105 apartments), resulting in 51 valid data points out of the 55 obtained. The Structural Equation Modeling (SEM) technique was used to analyze the data, method Partial Last Square using PLS-SEM software as a tool. The results obtained from the statistical analysis of the data collected showed that 4 of the 7 hypotheses formulated were confirmed. The Built Environment has use value in consumer perception, unlike Sustainability. Sustainability is a construct that has an impact on Willingness to Pay, unlike the Built Environment. Some indirect effects were noted, but it can be said that the low level of knowledge on the subject of sustainability negatively affects Willingness to Pay and Purchase Intention for sustainable properties. As far as theory is concerned, the study serves as a start and an indication for future research in an area that is still little explored in Brazil. From a managerial point of view, the research insights serve as a basis for construction companies to direct new strategies in the search for greater consumer engagement with the issue of sustainability. This greater engagement will consequently lead to greater word of mouth, purchase intent and a willingness to pay more for sustainable properties, ensuring greater profitability. [resumo fornecido pelo autor]
O aumento da população em centros urbanos gera cada vez mais problemas ao meio ambiente: redução de áreas verdes, poluição do ar e água, mudanças climáticas. Aumento que traz uma maior necessidade por imóveis residenciais, estimulando a indústria da construção civil e maior competitividade nas empresas do ramo. Assim, é fundamental que a construção civil se torne mais sustentável minimizando os impactos no meio ambiente, bem como entender melhor a relação do consumidor com os conceitos de sustentabilidade para que as empresas possam direcionar seus investimentos de forma assertiva e conquistar clientes. Essa pesquisa investiga a relação entre as dimensões sustentabilidade e o ambiente construído com as dimensões de comportamento do consumidor de edificações sustentáveis: disposição a pagar, intenção de compra, valor de uso e boca a boca. A pesquisa possui natureza quantitativa-descritiva com utilização de survey, aplicada em edificações multifamiliares em uma cidade da serra gaúcha (105 apartamentos), resultando em 51 dados válidos dos 55 obtidos. Para análise dos dados, foi utilizada a técnica de Modelagem de Equações Estruturais (MEE), método Partial Last Square com o software PLS-SEM como ferramenta. Os resultados obtidos com as análises estatísticas dos dados coletados demonstraram a confirmação de 4 das 7 hipóteses formuladas. O Ambiente Construído possui valor de uso na percepção do consumidor, ao contrário da Sustentabilidade. Já a Sustentabilidade é um construto que tem impacto na Disposição a Pagar, ao contrário do Ambiente Construído. Foram percebidos alguns efeitos indiretos, no entanto, pode-se dizer que o baixo nível de conhecimento sobre o tema Sustentabilidade, interfere negativamente na Disposição a Pagar e Intenção de Compra de imóveis sustentáveis. Para a teoria, o estudo serve de start e indicação para futuras pesquisas em uma área ainda pouco explorada no Brasil. Sob o ponto de vista gerencial, os insights da pesquisa servem de base para as construtoras direcionarem novas estratégias, na busca de maior engajamento dos consumidores com o tema sustentabilidade. Esse maior engajamento, trará consequentemente maior boca a boca, intenção de compra e disposição a pagar mais por imóveis sustentáveis, garantindo maior lucratividade. [resumo fornecido pelo autor]
Keywords: Comportamento do consumidor; Edifícios sustentáveis; Sustentabilidade; Administração; Consumer behavior; Sustainable buildings; Sustainability; Management